THE EFFECT OF PSYCHOLOGY TRAITS ON STUDENTS SPEAKING ACHIEVEMENT - Thresia Marisca; Johan Sinulingga (Universitas Negeri Medan, 2012)
ABSTRACT This study aims to find out the effect of Psychology Trait on Students’ Speaking Achievement. The population of the study was the second year students in the academic year 2011 / 2012 at SMP HKBP Medan in two classes with a total of 64 students. Ten students were selected by using random sampling technique. The first group (5 students) was the extrovert group, while the second group (5 students) was the introvert group. The instruments of collecting data were questionnaire and oral test. The data were analyzed by using the Kruskal Wallis Test. The result of the analysis showed that the H = X2 value was higher than chi square table value (4.81 > 3.94) at the level of significance 0.05 with a freedom degree of 10. It means that there was a significance effect of Psychology Traits on Students’ Achievement in Speaking. Key Words: Pschology Traits, Speaking, Introvert, Extrovert.